The current crisis intensifies the economic contrasts in the world's major cities. driven by the pandemic, and other negative aspects (Revista de Investigaciones Universidad del Quindío, 2022)
The general objective of this research was to determine the probable mechanisms to counteract the impoverishing effects and whose confluence is driving the current crisis, through scientific and technological advances to move towards a more equitable economy, with less income inequality between social groups and less social mobility to move towards a more equitable economy,  with lower income inequality between social groups and less social mobility. The methodology of Kitchenham (2004) was used to carry out a Systematic Literature Review (RSL). The PICOC framework was used to identify the central elements of the research question (Booth, Sutton, & Papaioannou, 2016)Some international organizations report that the crisis caused by the COVID 19 pandemic will continue until 2030. Well, 2020 was recharged in the poorest and most vulnerable. The World Bank calls "chronic poor" - rural population dedicated to agriculture and livestock - with the pandemic new poor were evidenced in the cities, among people with higher educational degrees, dedicated to services, construction and manufacturing, and especially in the younger population.The World Bank projects that in the long run the crisis is likely to increase inequality within countries, the economy had its biggest drop in 90 years and millions of people lost their jobs. And he emphasizes that the pandemic, armed conflicts and climate change are the 3 factors whose confluence is driving the current crisis and its impact will extend into the future.The World Bank also reports that even if we are optimistic, the impoverishing effects of the pandemic will be colossal. And that the tech billionaires bulged their wealth in the midst of the crisis.
Keywords: pandemic; poverty; climate change; armed conflict